PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, LEVERAGE DAN LIKUDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL KONTROL - Ilya, Rara Rahmadani; Sugiarto, Sugiarto; Lestari, Puji; Irianto, Bambang Setyobudi (Jurnal Riset Akuntansi Soedirman, 2024)
This study aims to analyze the effect of corporate social responsibility, company size, sales growth, leverage, liquidity on firm value with profitability as the control variable, using a quantitative approach with the research population being non-cyclical consumer sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period totaling 135 companies. The sampling technique obtained Analyzed using multiple linear analysis regression tests through IBM SPSS 26. Based on the results of data analysis found that: 1) Corporate social responsibility has no effect on firm value, 2) Company size has no effect on firm value, 3) Sales growth has no effect on firm value, 4) Leverage has a negative effect on firm value, 5) Likuditas has no effect on firm value. The implication of the research is that in an effort to increase the value of the company, company management can continue to pay attention to managing its debt properly in order to generate profits. In addition, it is hoped that the results of this study can be used as material for consideration for management, investors or other interested parties in making investment decisions and policies so as to produce optimal investment and in assessing the value of a company.